An Assessment of Technology Development Initiatives of Tool Industry in the Region - Singh, Davinder (My University, 2009)
In today’s competitive business environment, global competition forces companies to perpetually seek ways of improving their products and services. The pressure on organizations to adapt to new technologies and external threats requires resourcefulness, creativity and innovation. The fierce competition situation arising out of globalization and liberalization is forcing the organizations across the globe to realize that their survival is not feasible in the absence of R&D and innovation practices. Markets have become more open, competitive and the customers more demanding. To stay close to the customers is essential for sustained growth and continuity of business. Without continuous technology upgradation, no enterprise can ever remain competitive. The rate of change is accelerating rapidly as new knowledge and global diffusion increase. The need of the hour is to deliver high quality products through continuous improvements in product features, bring new products to the market faster, make product changes faster and more manageable, improve forecasting accuracy of the product demands, reduce costs, improve employee training, skills and education levels, improve information systems and networks, achieve greater flexibility of manufacturing functions. Organizations that want to survive in today’s highly competitive business environment must address the need for high quality, lower costs, and more effective and swifter research and development. These formidable changes have forced the organizations around the world to adopt innovative and state of the art strategies to suitably address the all-important issues of organization survival, growth and excellence. The key driver of organization’s ability to change is innovation. Thus the organizations are left with no choice but to upgrade the existing systems, products and technologies for their survival. The present work explains that creativity and innovation are the necessary ingredients for developing new technology. The study presents a detailed analysis of the various factors and issues affecting technology development initiatives of tool industry in the region and their relative significance in affecting improvements.
M.E. (Production and Industrial Engineering)
Keywords: Small Scale Sector; Cutting Tool Industry; Technology Development; Development Indicators